A Qualitative Study on E-Reviews of Mid-Segment Hotels (e-Review of Tourism Research, 2022)
The main purpose of this study is to evaluate the e-reviews for the mid-segment hotels of Mussoorie and to explore the major themes addressed by the consumers in the e-reviews. The qualitative data in the form of user-generated e-reviews was acknowledged through TripAdvisor.com. The data was collected for the past six months, i.e., from December 2021 to June 2022. A total of 993 reviews have been analyzed using the content analysis technique and RQDA (R Qualitative Data Analysis) package of R software to explore positive and negative e-reviews and evolve the top discussed themes of the e-reviews. The results revealed the categorization of e-reviews into positive and negative categories and highlighted the major aspects of these e-reviews to be addressed. Frequencies of the top-used words in both positive and negative e-reviews have been evaluated. Top themes discussed in the e-reviews have also been identified to provide significant insights into the hotel industry. The study encapsulates e-reviews given by those tourists who particularly stayed in mid-segment hotels. The data was collected from one travel portal site Trip Advisor.com for a relatively short period. Further studies should include more data by incorporating the other hotel categories. The study reveals some significant insights for mid-segment hotel management at the hill station of Mussoorie to attract and improve the tourist inflow.